Kebun Teh sebagai Destinasi Ekowisata Alam di Lebak Banten - Patmawati, Eulis (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to compile a systematic description of ecotourism development in the area by reviewing literature from seven relevant academic sources. Through the systematic review method, this study identified the main dimensions that support ecotourism development, namely: community empowerment based on local wisdom, branding and promotion strategies for tourist destinations, active community participation, quality of services and tourist attractions, and strengthening supporting infrastructure. The results of the analysis show that the development of the Cikuya Tea Plantation as an ecotourism destination is highly dependent on the synergy between environmental conservation and social involvement of the surrounding community. Educational activities such as local tea processing, preservation of endemic flora in the damar forest, and trekking to the Ciporolak Waterfall can be the main attractions that have ecological and economic value. The study also found that the lack of strong digital promotion and suboptimal access infrastructure were the main obstacles. However, with interpersonal communication strategies, strengthening local identity (local branding), and cross-actor collaboration, this area can be developed as a sustainable community-based ecotourism model. In addition, this study recommends the development of integrated tourism packages, local human resource training, and the integration of Cikuya Tea Plantation into the wider Lebak geopark and cultural tourism network. With an inclusive approach based on local wisdom, Cikuya Tea Plantation has the potential to become an icon of environmentally friendly tourism that also preserves Baduy cultural values ​​and Banten's biodiversity.